2006
DOI: 10.3168/jds.s0022-0302(06)72269-x
|View full text |Cite
|
Sign up to set email alerts
|

Yields and Persistency of Lactation in Friesian and Jersey Cows Milked Once Daily

Abstract: Effects of milking cows once daily throughout lactation at high stocking rates (17% more cows/ha than for those milked twice daily) were studied in 2 Friesian and 2 Jersey herds during 3 lactations. Cows were allocated to 2 herds within breed and were milked either once or twice daily, based on age, genetic merit, and previous performance. Cows remained in their original herd and were milked at the same milking frequency during all lactations. Culled cows (20% per year) were replaced by 2-yr-old heifers. Yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 14 publications
4
30
1
1
Order By: Relevance
“…Moreover, milk yield in M-DIM60 group was lower (P ≤ 0.01) than in H-DIM200 group (Table 4). The results of the UFL = 7200 kcal NEL, NEL = netto energy for lactation, UFL = feed unit for lactation, PDIN = protein digested in the small intestine supplied by rumen-undegraded dietary protein and by microbial protein from rumen-degraded organic matter, PDIE = protein digested in the small intestine supplied by rumen-undegraded dietary protein and by microbial protein from rumen-fermented organic matter, LFU = fill unit for lactating dairy cows, ADF = acid-detergent fibre, NDF = neutraldetergent fibre study are in agreement with the results showed by Hickson et al (2006) indicating negative correlation between lactation duration and peak yield in the Friesians.…”
Section: Resultssupporting
confidence: 80%
“…Moreover, milk yield in M-DIM60 group was lower (P ≤ 0.01) than in H-DIM200 group (Table 4). The results of the UFL = 7200 kcal NEL, NEL = netto energy for lactation, UFL = feed unit for lactation, PDIN = protein digested in the small intestine supplied by rumen-undegraded dietary protein and by microbial protein from rumen-degraded organic matter, PDIE = protein digested in the small intestine supplied by rumen-undegraded dietary protein and by microbial protein from rumen-fermented organic matter, LFU = fill unit for lactating dairy cows, ADF = acid-detergent fibre, NDF = neutraldetergent fibre study are in agreement with the results showed by Hickson et al (2006) indicating negative correlation between lactation duration and peak yield in the Friesians.…”
Section: Resultssupporting
confidence: 80%
“…In addition, the decline in daily milk yield (c) was highest with the Holstein cows, indicating a less persistent lactation profile than for the J Â HF cows. This is consistent with the findings of Hickson et al (2006), who reported higher lactation persistency in pure bred Jersey dairy cows compared with Friesian dairy cows. Although there were subtle differences between genotypes in the shape of the fat plus protein yield lactation curve, neither peak yield, nor the rate of decline after the peak differed between genotypes, with this reflected in the absence of a genotype effect on full lactation fat plus protein yield.…”
Section: Milk Production and Compositionsupporting
confidence: 95%
“…According to Cole & VanRaden (2006), genetic selection for persistency of lactation may become an important technology in the future; therefore, it should be considered in selection objectives to improve the productive efficiency of dairy herds (Hickson et al, 2006).…”
Section: Resultsmentioning
confidence: 99%